2017
DOI: 10.1111/irv.12464
|View full text |Cite
|
Sign up to set email alerts
|

Influenza in long‐term care facilities

Abstract: Long‐term care facility environments and the vulnerability of their residents provide a setting conducive to the rapid spread of influenza virus and other respiratory pathogens. Infections may be introduced by staff, visitors or new or transferred residents, and outbreaks of influenza in such settings can have devastating consequences for individuals, as well as placing extra strain on health services. As the population ages over the coming decades, increased provision of such facilities seems likely. The need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
117
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 104 publications
4
117
0
6
Order By: Relevance
“…19 Advantages of notifying PHUs may include receiving expert advice on the nuances of infection control, facilitating laboratory testing/chasing results, promotion of immunisation and moral support in the face of resistance to social distancing/visitor restriction. 1,25,26 Of relevance to our current findings, a meta-analysis by Darvishian demonstrated the efficacy of influenza vaccination for the elderly in the setting of an epidemic season and even in the face of poor vaccine match. Furthermore, in our LHDs, PHUs can facilitate access to anti-viral medication.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…19 Advantages of notifying PHUs may include receiving expert advice on the nuances of infection control, facilitating laboratory testing/chasing results, promotion of immunisation and moral support in the face of resistance to social distancing/visitor restriction. 1,25,26 Of relevance to our current findings, a meta-analysis by Darvishian demonstrated the efficacy of influenza vaccination for the elderly in the setting of an epidemic season and even in the face of poor vaccine match. Furthermore, in our LHDs, PHUs can facilitate access to anti-viral medication.…”
Section: Discussionsupporting
confidence: 50%
“…1,11 One example is that different facility layouts might facilitate outbreak propagation or control, but it is difficult to obtain and analyse meaningful information on this qualitative factor. Studies in this area are subject to confounding effects from multiple covariates, not all of which can be easily measured.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute respiratory virus infection outbreaks are a common problem in NHs. 28,29 A recent systematic review reported a 1.21% to 85.2% annual incidence of influenza or RSV infection in long-term care facilities. 28 Other than influenza and RSV, human metapneumovirus is the third most common causative pathogen for NH respiratory infection outbreaks.…”
Section: Discussionmentioning
confidence: 99%